Consumer Impressions of the Safety and Effectiveness of OTC Medicines - Jeffrey Gordon Taylor; Stephen Ayosanmi; Sujit S. Sansgiry (MDPI AG, 2023)
The public generally believes OTC medicines to be helpful for treating minor ailments. From a survey point of view, that position often originates from feedback obtained when these medicines are considered as one broad category. The objective of the study was to assess the properties of 15 categories of agents across three dimensions-effectiveness, safety, and familiarity. Data were gathered via an online non-random survey in one Canadian province, where residents were asked to consider 15 OTC medicine categories in terms of those dimensions. Five hundred and seventy-five completed surveys were obtained out of 3000 sent. On the 10-point effectiveness scale, values ranged from 5.1 (Athlete's foot cream) to 7.3 (headache medicine). For safety, the medicines were closely grouped (6.0 to 7.4). Cough syrups for children were perceived as less safe than those for adults. There was a trend in that, as product familiarity grew, so did impressions of safety and effectiveness. The results support other reports where OTC medicines are described as safe and effective, although safety ratings were not particularly high. Responders considered these medicines to generally be higher in safety than effectiveness.